Quality of Kefir Combination Between of Goat's Milk and Skim Milk on Variations of Sugar and Fermentation Duration - Kurniawati, Erna; Suryani, Titik (Universitas Muhammadiyah Surakarta, 2023)
Kefir is a probiotic bevarage produced by live lactic acid bacteria. One of the innovative ingredients for kefir is goat's milk, skim milk, and variations of sugar (cane sugar and palm sugar). The nutritional content of goat's milk is 2.2% protein, 14.7% fat, and 3% fiber, and 4.80% lactose. The addition of skim milk in the manufacture of kefir can increase the total sugar content. The addition of sugar as a source of nutrition for kefir grain starter bacteria. The purpose of this study was to quality of kefir combination between of goat’s milk and skim milk on variations of sugar and fermentation duration. This study used an experimental method and a completely randomized design (CRD) with two factors. The first factor is the variations of sugar (A) palm sugar and cane sugar. Factor II (B) is the variations of fermentation duration for 24 hour, 36 hour, and 48 hour. The results showed that the best total kefir acid content combined with goat milk and skim milk was 0.797%, pH 4 in the A2B1 treatment (30 g cane sugar + 24 hour of fermentation duration). The best organoleptic quality was in the A2B1 treatment (30 g cane sugar + 24 hour of fermentation duration) with a sour taste, white color, tasty flavour, and soft texture.